Identification of water conservative tree species with high economic value around â€œSendang Kalimah Toyyibahâ€ - Wiryani, Erry; Anggoro, Sutrisno; Mulyani, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Spring conservation require serious concern on the economic advantages for the society. Without economic advantages achieved from the conservation activities, the conservation programme should face intense conflict of land utilization. Plantation of economically valuable conservative plant species is one of the proposed solution to overcome the problem. This research aimed to identify the economic value of conservative plant species found in â€œSendang Kalimah Toyyibahâ€ surrounding. Research was conducted through field observation involving 4 line transects and 4 square transects at each line with transect size of 20 m x 20 m. Plant identification was conducted for tree strata. Data analysis was including diversity, evenness and importance index of respective plants. Economic valuation was conducted through literature study. The result showed there were 28 plants species availabile in â€œSendang Kalimah Toyyibahâ€ surrounding. Among the plant species 22 of the had been identified to provide conservative function, while 6 of them werenâ€™t including Banana, Papaya, Melinjo, Pangi, Longan and Stink Bean. Instead of providing conservative function, most plants also provide economic advantages including wood, fruit, flower, bud, leaf, fibre, sugar, peel and bean products while only 3 of them were not identified including Banyan, Manila Tamarind and Amboyna Wood. Plantation of economically valuable conservative plant species is recommended to support the conservation of the spring as well as to provide economic advantage for the society.Â Keywords: conservation, economic, plant, â€œSendang Kalimah Toyyibahâ€, spring